DETERMINANTS OF THE INTENTION TO PAY ZAKAT ONLINE: THE CASE OF INDONESIA - Rahmatina A. Kasri; Meis Winih Sosianti (Journal of Islamic Monetary Economics and Finance, 2023)
In this paper, we extend the Unified Theory of Acceptance and Use of Technology (UTAUT) model to examine factors that shape the intention of Muslims in Indonesia to pay zakat online. In the analysis, we include performance expectancy, effort expectancy, social influence, facilitating conditions, trust in zakat institutions, zakat literacy and Islamic religiosity as potential factors. The study employs primary data gathered from 734 respondents and uses the Structural Equation Modeling (SEM) method for data analysis. The main result shows that facilitating conditions, performance expectancy, trust in zakat institutions, social influence, and zakat literacy influence the intention to pay zakat online. However, effort expectancy and Islamic religiosity turn out to be insignificant determinants of the intention to pay online zakat. The findings suggest that zakat stakeholders must enhance trust and intensify education about zakat. Zakat organizations must also improve the quality of the online zakat system, highlight the benefits of zakat online, and optimize the use of social media to increase zakat collection through digital channels.